Detection and assessment of electrocution in endangered raptors by infrared thermography - Melero Asensio, Mar; González, Fernando; Nicolás, Olga; López, Irene; Jiménez Martínez, María De Los Ángeles; Jato Sánchez, Susana; Sánchez-Vizcaíno Rodríguez, José Manuel (BMC Veterinary Research, 2013)
BACKGROUND Most European birds of prey find themselves in a poor state of conservation, with electrocution as one of the most frequent causes of unnatural death. Since early detection of electrocution is difficult, treatment is usually implemented late, which reduces its effectiveness. By considering that electrocution reduces tissue temperature, it may be detectable by thermography, which would allow a more rapid identification. Three individuals from three endangered raptor species [Spanish imperial eagle (Aquila adalberti), Lammergeier (Gypaetus barbatus) and Osprey (Pandion haliaetus)] were studied thermographically from the time they were admitted to a rehabilitation centre to the time their clinical cases were resolved. CASES PRESENTATION The three raptors presented lesions lacking thermal bilateral symmetry and were consistent with electrocution of feet, wings and eyes, visible by thermography before than clinically; lesions were well-defined and showed a lower temperature than the surrounding tissue. Some lesions evolved thermally and clinically until the appearance of normal tissue recovered, while others evolved and became necrotic. A histopathological analysis of a damaged finger amputated off a Lammergeier, and the necropsy and histopathology examination of an osprey, confirmed the electrocution diagnosis. CONCLUSIONS These results suggest that thermography is effective and useful for the objective and early detection and monitoring of electrocuted birds, and that it may prove especially useful for examining live animals that require no amputation or cannot be subjected to invasive histopathology. Centro de Vigilancia Sanitaria Veterinaria (VISAVET) TRUE pub